2015
DOI: 10.1002/eqe.2535
|View full text |Cite
|
Sign up to set email alerts
|

Critical limit states in seismic buckling‐restrained brace and connection designs

Abstract: Summary A welded end‐slot buckling‐restrained brace (WES‐BRB) has been developed at the Taiwan National Center for Research on Earthquake Engineering (NCREE). A steel frame equipped with a WES‐BRB can offer a cost‐effective solution to meet interstory drift and earthquake‐resistant design requirements for seismic steel buildings. According to the WES‐BRB and connection design procedure proposed by NCREE, there are seven key elements of a buckling‐restrained braced frame (BRBF) design that require design checki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed. These findings [15][16][17][18][19][20][21] all highlighted the negative effect of braced frame seismic deformations on the performance of BRB connection zones. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed. These findings [15][16][17][18][19][20][21] all highlighted the negative effect of braced frame seismic deformations on the performance of BRB connection zones. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20].…”
Section: Introductionmentioning
confidence: 92%
“…The subassemblage tests by Tremblay et al [14] showed that BRB end rotation would cause additional inplane flexural stress on BRB casing. The gusset plate design considering the combined effect of brace action and frame action forces was investigated theoretically and numerically [18][19][20]. The frame tests by Lin et al [15], Chou et al [16], and Palmer et al [17] showed that in-plane frame action force at the beam-column-gusset interface was observed.…”
Section: Introductionmentioning
confidence: 99%
“…The BRB steel cores were fabricated from ASTM A572 GR50 steel plate (345 MPa nominal yield stress). The nine design limit states for the BRB and connection, including the BRB steel casing flexural buckling, gusset tension yielding or compression buckling, and gusset interface strength have been documented in the reference [11]. The restrainers in specimens WT-BS and WT-BD were fabricated from 216.3 × 4 mm and 190.7 × 4 mm circular pipes respectively.…”
Section: Design Of Buckling-restrained Brace and Steel Framementioning
confidence: 99%
“…The RC column axial load capacity was sufficient to resist axial load demands arising from structure overturning and BRBF force. Therefore, the simplified procedure using the soften strutand-tie (SST) model proposed by Hwang and Lee [30] was adopted in this study to effectively evaluate the diagonal compressive strength C d of the RC member D-regions: (11) where: ζ = cracked concrete softening coefficient; f c = concrete compressive strength; A str = effective area of the diagonal strut; K = strut-and-tie index representing the beneficial effects of the tie reinforcement on the shear strength. The discontinuity regions (D-regions) in RC members are subjected to disturbance in the flow of internal forces.…”
Section: Strength Checks Of Reinforced Concrete Framementioning
confidence: 99%
See 1 more Smart Citation